Gamifying English Learning and Assessment to Reduce Anxiety and Foster Speaking Skills: The Case of Secondary School Students - D’Adamo, Francesca (ALLiED, 2025)
In Italy, the prevailing challenge for students lies in the intense pressure experienced during oral and written tests, emerging as a primary source of anxiety and stress within the educational environment. Moreover, despite significant investment in learning English as a foreign language (EFL), students often face frustration and demotivation due to inadequate language competence. This paper explores the potential of gamification to engage students and enhance their comfort and confidence in the learning process. Drawing on game-informed theories, gamification is viewed as a tool capable of fostering autonomy, competence, and relatedness in learning, redirecting students’ efforts towards goal attainment, and leveraging motivation through explicit feedback, recognition, and rewards. However, studies emphasise the critical importance of careful design, acknowledging the complexity of student motivation and the potential variability in the effectiveness of gameful learning strategies. While gamification has gained attention in recent years, its application as an assessment and design tool in Italian EFL programs remains underexplored. The article presents the outcomes of a qualitative case study involving 27 Italian secondary public school students aged 15-18. The research demonstrates positive and promising results in favour of gamification by utilising tools such as surveys, interviews, focus groups, and participant observation. The findings highlight its positive impact on student motivation, language competence, and the implementation of accessible assessment procedures to lower school anxiety.